2010
DOI: 10.2478/s11534-009-0140-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic cluster developement in In1−x MnxSb semiconductor alloys

Abstract: Abstract:X-ray Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Transmission Electron Microscopy (TEM) and magnetic measurements as a function of applied magnetic field and temperature for In 1− Mn Sb (0.05 0.2) system are reported. Magnetic measurements performed at high and small magnetic field in ZFC and FC indicate the coexistence of ferromagnetic In 1− Mn Sb solid solution and two types of magnetic cluster: ferromagnetic MnSb and ferrimagnetic Mn 2 Sb. XPS valence band and Mn 2p core level spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Basically, the MS-RT sample shows the highest and values, while the decrease of and incorporation of polymer lead to the decrease of the corresponding parameters. It should be noted, that previous studies of 30-nm MnSb nanoparticles reported emu/cm 50 , which is lower than the bulk MnSb value (about 700 emu/cm 33 , 34 ), but close to that for the MS-RT sample with similar mean crystallite size, while the value in our case is 1.5 times smaller than the one reported earlier 50 . For the sample MS-LT* we observed the lowest and values, while the rest of studied samples demonstrate closer values, in the range of 160–250 Oe, and ratio is in the range of 0.41–0.76.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Basically, the MS-RT sample shows the highest and values, while the decrease of and incorporation of polymer lead to the decrease of the corresponding parameters. It should be noted, that previous studies of 30-nm MnSb nanoparticles reported emu/cm 50 , which is lower than the bulk MnSb value (about 700 emu/cm 33 , 34 ), but close to that for the MS-RT sample with similar mean crystallite size, while the value in our case is 1.5 times smaller than the one reported earlier 50 . For the sample MS-LT* we observed the lowest and values, while the rest of studied samples demonstrate closer values, in the range of 160–250 Oe, and ratio is in the range of 0.41–0.76.…”
Section: Resultssupporting
confidence: 58%
“…Bulk MnSb is a FM semimetal with °C 31 , 32 and room temperature saturation magnetization emu/cm 33 , 34 . The increase of Mn atoms excess in the Mn Sb compound leads to the considerable decrease of and values 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although the ab initio calculation has been used to obtain the In1-xMnxSb system properties in the entire range of compositions [7], experimentally it has been noted that manganese solubility in InSb is limited. InSb and MnSb thus form an eutectic [8], and the presence of clusters with manganese has been found in solid polycrystalline In1-xMnxSb solutions obtained by fusion of InSb with Mn [9,10] and by fusion of the constituent elements with argon arc [11].…”
Section: Introductionmentioning
confidence: 95%
“…On the one hand, obtaining In1-xMnxSb system alloys with high Mn concentrations has not been possible using techniques such as the fusion of InSb with Mn [9,10] or the fusion of the constituent elements with the argon arc [11]. On the other hand, the usefulness of a material in spintronic applications depends on its magnetic properties, which are closely related to its morphological, structural and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…There are many ways to prepare inhomogeneous and disordered solid-state systems. One of ways is based on applying two-component systems, in which components are characterized by a limited solubility and can form eutectic alloys [16][17][18].…”
Section: Introductionmentioning
confidence: 99%